La gestión de cobranzas y su impacto en la liquidez y rentabilidad de DAISCORP CIA LTDA - Lazo Cárdenas, Yoselin Stefanía (2024)
The research entitled "Collection management and its impact on the liquidity and profitability of Daiscorp Cía Ltda." examines how efficient collection practices can directly influence the company's financial situation. The study focuses on the importance of proper accounts receivable management to ensure that the company maintains healthy levels of liquidity and profitability. Collection management involves a set of procedures and policies that the company implements to ensure that payments from its customers are received in a timely and complete manner. This process is crucial, as late or non-compliance with payments can negatively affect the company's ability to meet its own financial obligations, which in turn could compromise its solvency and financial stability....